Análisis socioeconómico de la parroquia La Esperanza del cantón Quevedo de la provincia de Los Ríos y su incidencia del impuesto a las exportaciones de banano - Arreaga Contreras, Juan Isaac (2017)
The Constitution of the Republic of Ecuador promulgated in 2008 clearly establishes that the state will promote food sovereignty and the generation of jobs by the various sectors, which is why the objective of this work was to develop a socio-economic analysis of the parish La Esperanza and determine the impact of the tax on banana exports in the same, in order to know and verify the reality in the area. Therefore we established the objectives that are fundamental for the development of the work and also defined the importance of the realization of the same and the possible socio-economic impact that would have as a basis to establish the justification of the work. The information was collected that would serve as a structural basis for the achievement of the work, so we proceeded to compile data to help clarify the situation of the subject under investigation……..